Averting Deforestation: Designing the Model of a Public Participation-Based Environmental Agreement of Shifting Functionality of Forest - Permadi, Iwan; Maharani, Diah Pawestri; Ayub, Zainal Amin (Universitas Negeri Semarang, 2023)
This research highlights the shifting concepts and mechanisms in business licensing in forest areas from environmental licensing to an environmental agreement following the effectuation of Indonesia’s Job Creation Law. It is important to investigate this change, considering that it may involve environmental damage or deforestation in forest areas, which tends to be pro-businesses. With the normative-juridical method that incorporates statutory, conceptual, and analytical approaches, This research aims to analyze the concept of the integration of an environmental agreement in risk-based business licensing that has changed business licensing into an environmental agreement in forestry. This study also analyzes the concept of an environmental agreement concept regarding the likelihood of deforestation and the shifting functionality of forest areas. The last important point is that it is paramount to set an ideal legal construction in the environmental agreement in risk-based business licensing in forestry businesses by employing a restorative justice approach and public participation. The research results recommend an ideal legal concept in the integration of an environmental agreement into risk-based business licensing by taking into account public participation, as outlined in Environmental Protection and Management Law, implying citizens to have both public and private rights, enabling them to participate. Moreover, the public role can adjust to the need and risk levels developed with varied concepts of the development of public participation by considering theories and practices in other countries.